Spectrophotometric determination for microamount of mercury (Ð†Ó€) and zinc(Ð†Ó€) from HCl media by Rhodamine 6G - Jawad, Shawket .K.; .Muslim, Nadia .M (Al-Qadisiyah Journal of Pure Science, 2017)
Rhodamine 6G used as anion exchanger in organic phase for extraction and spectrophotometric determination of Hg2+ and Zn2+ ions from HCl aqueous media after conversion metal ions into chlorol complexes anion .The study include limitation optimum condition for extraction such as , HCl concentration , metal ion concentration shaking time as well as stoichiometry of ion pair complex extracted , organic solvent effect , thermodynamic studies about extraction was endothermic for both metal ions ; in addition to another studies and applications for determination analyte metal in different samples .